Vozes emergentes: uma leitura do romance "Um rio chamado tempo, uma casa chamada terra", de Mia Couto - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
This assignment has as object to analyse the voices that come up on culture of Yoruba and Bantu matrix on the novel Um rio chamado tempo, uma casa chamada terra (2003) (a River Called Time, a home called earth), specifically analysing the recreation of some African myths on this Mia Couto s novel, through the dialogues between the myths created by the people of Yoruba and Bantu language, and those worshiped by Mia Couto s fictitious characters, especially in ritualistic aspects and the means used on transmission of oral tradition. In chapter one, there is a short concept of Mozambique under Portuguese colonial regime. There is also a reflexion about the role of literary critics that represent this Portuguese colony, between 1959 and 1974, trying to understand through this reflexion the importance of these Mozambican novelists on the building of this literature. There is an argument for about the importance of Mia Couto to Mozambican literature. In chapter two, it is spoken about the social place of Mozambican women on post-colonial society. In chapter three, the last one, which is the core of this assignment, it is analysed the recreation of some myths of Yoruba and Bantu people, defending the thesis that Mia Couto s novel is in favour of cultural hybridism and in this way these myths are reshaped as a literary strategy on the building of Mozambican identity. Besides, the interaction between the elements of African tradition and modernity made by Mia Couto throughout his novel, suggests that the construction of Mozambique future must give importance to the dialogue, painful but necessary, between the present and the past, i.e. the values and knowledge got from a mythic past, the worship to our ancestors that pass to the living the knowledge and laws to get a social junction. The theoretical argument is based on Henri Junod s concepts in his novel Usos e costumes dos bantos: a vida duma tribo do sul da África (1974), (the customs of the Bantus: a day in the life of a South African tribe), where the author makes a vast search about the Bantu culture. On the novels Orixás (1980) by Pierre Verger, Mito e realidade (1998) (Myth and Truth) by Mircea Eliade and, finally Mitologia dos Orixás (2002) (Mythology of Orixas) by Reginaldo Prandi, which are about the myths created by the people of Yoruba language supplemented by other works needed to back up the arguments developed on this assignment. It is highlighted that the cultures of Yoruba and Bantu matrix are articulated in the narrative of this novel: the tradition of storytelling, African rituals, respect for the family, for tradition, for our elders and dead, and recreated myths too. So, Mia Couto, through native narrators, longs for the restoring of ―the denied voice and the disfigured face‖ of these women and men in the history of contemporary African literature in Portuguese. Therefore, Mia Couto s works are of interest to cultural and literary studies because they bring the silenced voices to the written space of this novel, to tell their stories and the stories of those who live under the domain of silence, in post-colonial Mozambique.
Keywords: Mia Couto; Literatura Africana de Língua Portuguesa; Mitos; Narrativas.; Mia Couto; African Literature of Portuguese Language; Myths; Narrative; LINGUÍSTICA, LETRAS E ARTES: LETRAS